Empowerment of Rugby as the Economic Driver for the MSMEs: In Collaboration with the Indonesian Rugby Union (PRUI) West Java - Cintyawati, Cici; Malik Akbar Rohandi, Mochamad; Tresna Gumelar, Eka; Muhamad Taufik, Rezi (KnE Social Sciences, 2023)
Prior literatures have found the beneficial impact of hosting sports event in enhancing economic growth, especially by applying the empowerment concept. Given the rationale, this study sets Garut City as one of the Indonesian cities, as a research object to explore how hosting sports events can empower the SMEs in enhancing their business growth. This study focuses on hosting Rugby events as a medium to empower the SMEs and to further introduce Rugby to the local community. This research employed qualitative approach using a participatory technique. This study aims to dig deeper into information related to the current issue faced by the SMEs, to collect more insights about alternative solutions, and finally to give empowerment programs as the solution for those issues. The following were the three main steps used in the empowerment program, counseling, training, and mentoring stages. These stages help the SMEs to gather more information, knowledge, and skills in running their business and are expected to help in enhancing their business performance in terms of their financial performance and business sustainability in the future. Keywords: Rugby, sports, MSMEs, empowerment, economic development